Conveyor Control System Product Calculation Based On Programmable Logic Controller - Sinka Wilyanti; Mauludi Manfaluthy; Karseno Karseno (Jurnal Teknik, 2019)
The purpose of this study is design and create a product counter control prototype control system based on a programmable logic controller. Using the ladder diagram programming language with cx-programmer 9.5 software that can be applied as commands in the PLC and produce an output that is used to control and drive the product counter conveyor prototype. This research begins with literature review, design and follows by assembly conveyor, DC motor, power supply, controller circuit, proximity sensor, digital counter and PLC. The measurement result is the speed of processing time of the parcel beam 1.51 second and 2.96 second removal of the sensor, sensor detection 7 cm, the accuracy of calculation of the number of products can calculate precisely and well. The test results show that the design of the tool can work well in the process of calculating the number of products.Keyword : Control System, conveyor, proximity sensor, DC motor